Enthalpy of helix–coil transition: Missing link in rationalizing the thermodynamics of helix-forming propensities of the amino acid residues - Richardson, John M. (National Academy of Sciences, 2005)
It is known that different amino acid residues have effects on the thermodynamic stability of an α-helix. The underlying mechanism for the thermodynamic helical propensity is not well understood. The major accepted hypothesis is the difference in the side-chain configurational entropy loss upon helix formation. However, the changes in the side-chain configurational entropy explain only part of the thermodynamic helical propensity, thus implying that there must be a difference in the enthalpy of helix–coil transition for different residues. This work provides an experimental test to this hypothesis. Direct calorimetric measurements of folding of a model host peptide in which the helix formation is induced by metal binding is applied to a wide range of residue types, both naturally occurring and nonnatural, at the guest site. Based on the calorimetric results for 12 peptides, it was found that indeed there is a difference in the enthalpy of helix–coil transition for different amino acid residues, and simple empirical rules that define these differences are presented. The obtained difference in the enthalpies of helix–coil transition complement the differences in configurational entropies and provide the complete thermodynamic characterization of the helix-forming tendencies.